The Main Character in Khaled Hosseini’s Novel The Kite Runner: An Interdisciplinary Analysis of Literary Work from the Psychological Standpoint - Saiful Akmal; Sabriyati Sabriyati (Proceedings of AICS - Social Sciences, 2017)
As one important element in novel, character takes a large space in the storyline. Therefore, in this paper, the main focus is to analyze the main character of The Kite Runner novel by referring the character types to literature and psychological concept. The Kite Runner is a novel written by Khaled Hosseini in 2003. In 2005, this novel successfully became the chart-topping book and was voted in 2006 as the reading group book of the year. In examining the main character of Amir from literary concept, we will analyze the character personality through: the main character’s background, the main character’s act, the main character’s say, the main character’s thought and how other characters react to the main character. With regard to the main character analysis from psychological point of view, we use fundamental dimension of personality of how the character gets energy, attention, decision making and lifestyle. The result of this analysis shows that many positive sides of the character that can be adapted by the reader. Specifically speaking, from the literary conception, the main character falls into round/dynamic type of character. On the other hand, in psychology conception, the main character shows many changes from time to time. In childhood age the main character adheres the INFJ type, during adolescent age the main character changes his personality into ENFJ, and at adulthood age, he transforms into ESTP personality. Keywords:main character, novel, literature, psychology.